PENGARUH UNSUR SINTAKSIS BAHASA INGGRIS TERHADAP PENGGUNAAN BAHASA INDONESIA IMIGRAN AFGANISTAN - Murnisma Murnisma (Universitas Hasanuddin, 2022)
This writing will examine the influence of English syntactic elements on the use of the Indonesian language by Afghan immigrants. This research is qualitative, that is researchers who are trying to obtain accurate data about the Indonesian structure of phrases and sentences of Afghan immigrants and analyzing the elements of Indonesian syntax of Afghan immigrants. The data collection in this research is library research and field research. The results of this research indicate that the Indonesian syntax of Afghan immigrants is influenced by English syntax, both at the phrase and sentence level. The finding of this research is English has the same sentence patterns as Indonesian, id est Subject + Predicate + Object. Indonesian sentence structure of Afghan immigrants always uses a copula verb between the subject and the complement, while the Indonesian sentence structure of Afghanistan Immigrants is patterned M (Menerangkan/explaining) – D (Diterangkan/explained) following the English phrases pattern.